1997
DOI: 10.1152/ajpendo.1997.273.4.e821
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic mass balance model for 1,5-anhydroglucitol: applications to monitoring of glycemic control

Abstract: The polyol 1,5-anhydroglucitol (AG) present in human plasma is derived largely from ingestion and is excreted unmetabolized. Reduction of plasma [AG] has been noted in diabetics and is due to accelerated excretion of AG during hyperglycemia. Plasma [AG] has therefore been proposed as a marker for glycemic control. A precise understanding of its utility relies on a quantitative understanding of the mass balance for AG. In this study, non-steady-state data from the literature were analyzed to develop a dynamic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 33 publications
3
47
0
2
Order By: Relevance
“…Such depletion has been observed to occur in severe hyperglycemia as a result of persistent glucosuria (19). Additionally, a dynamic mass balance two-compartment model has been developed for 1,5AG (20), and it demonstrates that the tissue compartment is two to three times the mass of the plasma compartment. Model estimates suggest that accelerated depletion of 1,5AG is associated with slow recovery upon the initial improvement of glycemia, because the body pool of 1,5AG represents ϳ5 weeks of normal dietary intake.…”
Section: Concordance Of Longitudinal Changesmentioning
confidence: 99%
“…Such depletion has been observed to occur in severe hyperglycemia as a result of persistent glucosuria (19). Additionally, a dynamic mass balance two-compartment model has been developed for 1,5AG (20), and it demonstrates that the tissue compartment is two to three times the mass of the plasma compartment. Model estimates suggest that accelerated depletion of 1,5AG is associated with slow recovery upon the initial improvement of glycemia, because the body pool of 1,5AG represents ϳ5 weeks of normal dietary intake.…”
Section: Concordance Of Longitudinal Changesmentioning
confidence: 99%
“…Subsequently, 1,5-AG urinary excretion is increased during hyperglycemia, and it results in a lowered plasma concentration (4). This explains its low plasma level in patients with poorly controlled diabetes.…”
mentioning
confidence: 99%
“…It has been reported that the average daily increase in serum 1,5-AG concentrations is constant at about 0.3 μg/mL, and is not influenced by treatment, age, body weight, or duration of DM [20]. In addition, the normalization of 1,5-AG concentrations from depleted states has been believed to require approximately 5 weeks even under continuous normoglycemic conditions [20,21]. Thus, the recovery of 1,5-AG concentrations in our surgical patients may have been slow, with a time scale of several weeks after feeding is initiated.…”
Section: Discussionmentioning
confidence: 99%